Self-development through peer guidance for youth in Bandan Hurip Village in determining their careers - Dian Nugraheni; Ghaza Fawwaz Ijlali Permana; Rohimansyah Rohimansyah (Universitas Pendidikan Indonesia, 2026)
The era of globalization, along with the lack of motivation and understanding among village youth in Laksana Mulya, Harapan Mulya, and Bandanpurwa hamlets regarding educational and career directions, is the main background for this community service. This Kuliah Kerja Nyata Berdampak (KKN-Berdampak) aims to provide insight, deepen adolescents' self-understanding, and equip them with basic skills in developing mature career plans. The implementation method uses a peer guidance approach that includes personal, social, learning, and career guidance. The implementation consists of three main stages: planning through observation, implementation through group discussions, and the creation of a